HEGEMONY ANALYSIS IN BUDI PEKERTI MOVIE USING ANTONIO GRAMSCI’S THEORY - Ratna Wulandari; Aulia Haris Firstiyanti; Aswarini Sentana (Asosiasi Dosen Muda Indonesia, 2024)
This paper provides an analysis of Budi Pekerti movie using the lens of Antonio Gramsci's Hegemony Theory. The movie, which focuses on promoting moral and character education, subtly mirrors the dynamics of cultural dominance and ideological control in society. By focusing on how social and cultural norms are reinforced in everyday life, the movie serves as an excellent representation of how dominant ideologies shape the behaviors, values, and perceptions of individuals. Through the framework of hegemony proposed by Gramsci, this research examines how power structures, social expectations, and cultural narratives play a role in the reinforcement of conformity to a hegemonic moral order. Ultimately, this paper explores how cultural products like Budi Pekerti play a role in reinforcing social norms and maintaining ideological control, shaping the moral compass of individuals within society.